Music as an interaction ritual: A post-cognitivist framework for understanding musical interaction within Jazz - Mosola, Bonga (College of Music, 2025)
Musical performance requires improvised interaction between performers. Though the degree of improvisation and the nature of interactions may vary between different types of music, it is clear that our ability for synchronized action and improvisation is integral to musical performance. Music is also a product of human interaction on a macro or societal/cultural level. But how can the interpersonal interaction within musicians be explained, what cognitive processes underpin this interaction and how does this fit in with our conceptions of music as a social product? This dissertation aims to explain the interaction that musicians engage in through a model based on Randall Collins' interaction ritual theory (2004) and a modification of Garret Michaelsen's (2019) model of divergent interactional strategies. It also explores the cognitive underpinnings of musical interaction from a post-cognitivist perspective – viewing cognition from an embodied and ecological standpoint.